Narcyzm i sprawstwo w kulturze artystycznej - Dziadzia, Bogusław (Humaniora. Czasopismo Internetowe, 2022)
Narcissism is a part of the cultural heritage. It reaches many areas of social life. As a cultural phenomenon, it reaches more profound and broader than psychological analyses would indicate. It has always been present in the biographies of people significant for the development of culture and art. The thesis in the text states that cultural achievements without narcissism would be much more modest than we can observe today. The conducted argument indicates the positive aspects of narcissism in the field of artistic culture. Praise of narcissism concerns agency in culture and art. Trying to determine the place of narcissism in art culture, I favor forgoing the one-sidedly negative perception of the phenomenon of narcissism. Narcissism here is one of the motivating factors